“En part égale”: Family, Inheritance, and Market Change in a Francophone Community on the Prairies, 1880-1940 - Sylvester, Ken (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1998)
This paper uses the fates of farm families in a southern Manitoba community to examine the evolution of nineteenth-century inheritance practice during the development of the Canadian prairies. In Montcalm, settlers from Quebec shared their new rural municipality with anglophones from eastern Ontario. While parents were originally committed to establishing as many of their progeny as possible, by the 1920s landholders tended to liquidate their assets for distribution among already independent middle-aged children. Generally, this meant that property was transferred in portable and individual bundles, and decisions on how to make a living were left to the inheriting generation. Aging parents still provided for their children's futures, but because their relationship to the market economy had changed, so too had their relationship to their children. While simplifying obligations between farm parents and children, market change increasingly expressed family ties in the language of the marketplace.